Eudragit®: A Versatile Family of Polymers for Hot Melt Extrusion and 3D Printing Processes in Pharmaceutics - Juliana dos Santos; Guilherme Silveira da Silva; Maiara Callegaro Velho; Ruy Carlos Ruver Beck (MDPI AG, 2021)
Eudragit® polymers are polymethacrylates highly used in pharmaceutics for the development of modified drug delivery systems. They are widely known due to their versatility with regards to chemical composition, solubility, and swelling properties. Moreover, Eudragit polymers are thermoplastic, and their use has been boosted in some production processes, such as hot melt extrusion (HME) and fused deposition modelling 3D printing, among other 3D printing techniques. Therefore, this review covers the studies using Eudragit polymers in the development of drug delivery systems produced by HME and 3D printing techniques over the last 10 years. Eudragit E has been the most used among them, mostly to formulate immediate release systems or as a taste-masker agent. On the other hand, Eudragit RS and Eudragit L100-55 have mainly been used to produce controlled and delayed release systems, respectively. The use of Eudragit polymers in these processes has frequently been devoted to producing solid dispersions and/or to prepare filaments to be 3D printed in different dosage forms. In this review, we highlight the countless possibilities offered by Eudragit polymers in HME and 3D printing, whether alone or in blends, discussing their prominence in the development of innovative modified drug release systems.